2011
DOI: 10.1186/1471-2334-11-309
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 expression on neutrophils and monocytes of septic patients: relation to the underlying infection and the implicated pathogen

Abstract: BackgroundCurrent knowledge on the exact ligand causing expression of TREM-1 on neutrophils and monocytes is limited. The present study aimed at the role of underlying infection and of the causative pathogen in the expression of TREM-1 in sepsis.MethodsPeripheral venous blood was sampled from 125 patients with sepsis and 88 with severe sepsis/septic shock. The causative pathogen was isolated in 91 patients. Patients were suffering from acute pyelonephritis, community-acquired pneumonia (CAP), intra-abdominal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…More recent work has provided evidence for an antiinflammatory-protective role of Ang-2; in a murine septic model pre-treatment with Ang-2 prolonged survival from lethal infection by Pseudomonas aeruginosa [13]. http Recent studies of the Hellenic Sepsis Study Group conducted in large cohorts of patients [14][15][16] provided evidence that early alterations of the innate and adaptive immune status in sepsis are present and associated with the type of underlying infection, underscoring a pivotal role of the type of infection in the personalized nature of sepsis pathogenesis. In this respect Kritselis and coworkers have shown that kinetics of circulating lipopolysaccharide (LPS) differ according to the type of underlying infection and are associated with final outcome [16].…”
Section: Introductionmentioning
confidence: 98%
“…More recent work has provided evidence for an antiinflammatory-protective role of Ang-2; in a murine septic model pre-treatment with Ang-2 prolonged survival from lethal infection by Pseudomonas aeruginosa [13]. http Recent studies of the Hellenic Sepsis Study Group conducted in large cohorts of patients [14][15][16] provided evidence that early alterations of the innate and adaptive immune status in sepsis are present and associated with the type of underlying infection, underscoring a pivotal role of the type of infection in the personalized nature of sepsis pathogenesis. In this respect Kritselis and coworkers have shown that kinetics of circulating lipopolysaccharide (LPS) differ according to the type of underlying infection and are associated with final outcome [16].…”
Section: Introductionmentioning
confidence: 98%
“…Stimulation of that receptor leads to the production of proinflammatory cytokines, mainly TNF-␣ and IL-8 (18); in parallel, the receptor is shed through cleavage from the cell membrane in a soluble form known as sTREM-1 (6). A recent publication of the Hellenic Sepsis Study Group showed that, when sepsis develops in the context of VAP, the expression of TREM-1 on circulating monocytes and on circulating neutrophils is decreased upon the transition from sepsis to severe sepsis/shock and this is a component of sepsis-induced immunoparalysis (13). The increase of the expression of TREM-1 on the cell membrane of monocytes, along with the increased production of sTREM-1 by monocytes, is another finding indicating the reversal of immunoparalysis of circulating monocytes achieved by the clarithromycin treatment.…”
Section: Figmentioning
confidence: 99%
“…Written consent was provided from patients or their first-degree relatives for patients unable to consent. None of the enrolled patients participated in a former study published by the Hellenic Sepsis Study Group [ 16 ].…”
Section: Methodsmentioning
confidence: 99%